2009
DOI: 10.1111/j.1365-2249.2009.04050.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of cyclophosphamide in rodent models of experimental allergic encephalomyelitis

Abstract: SummaryIn this study, we have evaluated the effects of cyclophosphamide on the development of experimental allergic encephalomyelitis (EAE) in four EAE rodent models: monophasic EAE in Lewis rats, protracted relapsing (PR)-EAE in DA rats, myelin oligodendrocyte protein (MOG)-induced EAE in C57Bl/6 mice and proteolipid protein (PLP)-induced EAE in Swiss/Jackson Laboratory (SJL) mice. Cyclophosphamide, administered either prophylactically or therapeutically, suppressed most strongly the clinical symptoms of PR-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…It was developed in 1971 by Teitelbaum and colleagues in the laboratory of M. Sela, who was conducting extensive studies (Ridge et al, 1985;Levine and Saltzman, 1986;Lublin et al, 1987;Tischner and Reichardt, 2007;Mangano et al, 2010;) Cyclophosphamide Yes Glucocorticoids…”
Section: Eae and Ms Treatment Successmentioning
confidence: 99%
See 1 more Smart Citation
“…It was developed in 1971 by Teitelbaum and colleagues in the laboratory of M. Sela, who was conducting extensive studies (Ridge et al, 1985;Levine and Saltzman, 1986;Lublin et al, 1987;Tischner and Reichardt, 2007;Mangano et al, 2010;) Cyclophosphamide Yes Glucocorticoids…”
Section: Eae and Ms Treatment Successmentioning
confidence: 99%
“…This has significant implications both for the presumed pathogenesis and for therapeutic opportunities. As regards the pathogenesis, such a restricted receptor use could imply an inciting or causative infectious agent such as a virus; it could also explain Tolerizing DNA vaccines (Waisman et al, 1996;Lobell et al, 1998;Selmaj et al, 2000) ( Bar-Or et al, 2007;Garren et al, 2008) Antibiotics with immunomodulatory and neuroprotective functions: minocycline (Brundula et al, 2002;Giuliani et al, 2005a,b) Zabad et al, 2007;Zhang et al, 2008) Immunosuppressants Azathioprine Cyclophosphamide Mitoxantrone (Blaszczyk et al, 1978) (Mangano et al, 2010) (Ridge et al, 1985;Lublin et al, 1987) Hauser Hafler et al, 1991;Noseworthy et al, 1993;van de Wyngaert et al, 2001;Hartung et al, 2002;Krapf et al, 2005;Massacesi et al, 2005;Smith et al, 2005;Casetta et al, 2007 Haematopoietic stem cell transplantation (Karussis et al, 1992;Karussis et al, 1993b;Burt et al, 1995;Burt et al, 1998;Karussis et al, 1999;van Bekkum, 2000;Cassiani-Ingoni et al, 2007) ( Muraro et al, 2003;Burt et al, 2009;Muraro and Uccelli, 2010;Pasquini et al, 2010) i.v. immunoglobulins (Achiron et al, 1994;Achiron et al, 2000;Ephrem et al, 2008) ( Achiron et al, 1998;Haas, 2000;Strasser-Fuchs et al, 2000;Katz et al, 2006) BJP CS Constantinescu et al…”
Section: Discrepancies Between Eae and Ms Treatment Successmentioning
confidence: 99%
“…Animals were immunized with subcutaneous injections of 100 g of myelin proteolipid protein 139-151 (PLP 139-151 ) (Peptides International, Louisville, KY) following established protocols (Hammer et al, 2013;Jackson et al, 2009;Mangano et al, 2009). PLP 139-151 was prepared by dissolving 100 g in 0.15 ml sterile phosphate buffered saline (PBS) and emulsifying with 0.15 ml incomplete Freund's adjuvant (Sigma-Aldrich, St. Louis, MO) plus 250 g Mycobacterium tuberculosis (H37RA, Difco Laboratories, Detroit, MI).…”
Section: Induction Of Rr-eaementioning
confidence: 99%
“…Open‐label studies have given conflicting results but it has been suggested to be beneficial in non‐responders to first‐line therapies or those with particularly aggressive MS (Weiner and Cohen 2002). A recent study has tested its use in four different EAE rodent models (Mangano et al. 2009).…”
Section: Other Agentsmentioning
confidence: 99%